Obligacje zamienne a akcje z perspektywy inwestora - Buczek, Sebastian (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Convertible bonds are one of many financial instruments. From an investor's perspective they allow to participate in growth of a stock's price on one side and they provide a fixed floor on the another. The market price of a convertible bond is linked to the market price of a stock. However the relationship between the market price of a bond and the market price of a stock is different on various levels of the market price of a stock. There are five phases of the market price of a bond behaviour. When the market price of a stock drops close to zero, the market price of a bond also approaches zero. In the next phases the market price of a bond behaves more and more like the market price of a stock. Some investors, like hedge funds, can benefit from changes in the market prices of a bond and a stock. If the conversion premium is relatively high, an investor should sell a convertible bond and buy a stock, if the premium is relatively low, an investor should execute opposite transactions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 65-72